Causes of Collapse of Q-factor and Consequences for DSP Applications - Misans, P.; Hauka, A. (Elektronika ir Elektrotechnika, 2005)
Implementation of digital resonator by using of analog prototype and bilinear transformation leads to the effect of collapse of Q-factor. This paper describes the cause of the collapse and presents the formula for calculation of collapse frequency. We also present a simplified method for the compensation of collapse. The main consequence of collapse effect is that the formal using of pre-warping of critical frequencies of analog prototype can be dangerous for the synthesis of digital filters. Ill. 5, bibl. 3(in English; summaries in Lithuanian, English and Russian).